Characterization of an Ascochyta disease of the invasive vine Araujia hortorum E. Fourn. (Apocynaceae) - Ramirez, Gustavo Hernán (2019)
Araujia hortorum E. Fourn. is native to South America, where it is a valued species. In contrast, in other parts of the world where it was introduced as an ornamental, it has become an invasive weed. In New Zealand, it has been targeted for biological control, and this motivated field surveys for fungal pathogens in its native range in Argentina. The etiology of a frequently encountered disease was studied. Affected plants showed round necrotic leaf spots, and sometimes defoliation. Pathogenicity tests were conducted, and Koch´s postulates were completed. Ascochyta araujiae Speg. was identified as the causal agent. Through inoculation tests conducted on other species within the Apocynaceae it was shown that this pathogen is not highly specific. All five non-target species tested were found to be susceptible to the disease.